Pengembangan Media Pembelajaran Powtoon Berbasis HOTS pada Pembelajaran IPA Materi Cuaca Kelas 3 di Sekolah Dasar - Anbar Fauziyyah; Prima Mutia Sari (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The purpose of this study was to create a product in the form of learning media. The end result of this The purpose of this research is to create a product in the form of learning media. The end result of this research is a HOTS-based Powtoon learning video in class 3 science learning at SDN Cililitan. The research method used is Research and Development (R&D) with the ADDIE model, which has five stages: analysis, design, development, implementation, and evaluation. Data is gathered using both qualitative and quantitative methods. Questionnaires were distributed to validators, educators, and students to collect quantitative data. Meanwhile, qualitative data were gathered through interviews, comments, and suggestions. The validation test results given by the media expert had an average of 87 percent, which was included in the very feasible category, and the validation test results given by the material expert had an average of 100 percent, which was also included in the very feasible category. The assessment of the educators response to the media yielded results of 80 percent in the very good category. The very good category was selected by 99.4 percent of students in their media evaluations. Finally, the HOTS-based Powtoon learning media in science learning for grade 3 at SDN Kramat Jati is appropriate for use in the learning process.